Golgi Protein 73 Promotes Angiogenesis in Hepatocellular Carcinoma - Yiming Liu; Xinyang Hu; Sining Zhou; Ting Sun; Feiyan Shen; Linghui Zeng (Research, 2024)
Golgi protein 73 (GP73), a resident protein of the Golgi apparatus, is notably elevated in hepatocellular carcinoma (HCC). While its critical role in remodeling the tumor microenvironment (TME) is recognized, the intricate mechanisms are not fully understood. This study reveals that GP73 in HCC cells interacts with prolyl hydroxylase-2 (PHD-2) in a competitive manner, thereby impeding the hydroxylation of hypoxia-induced factor-1α (HIF-1α). The effect above promotes the production and secretion of vascular endothelial growth factor A (VEGFA). Moreover, exosomal GP73 derived from HCC cells can be internalized by human umbilical vein endothelial cells (HUVECs) and competitively interact with HECTD1, an E3 ubiquitin ligase targeting growth factor receptor-bound protein 2 (GRB2). This interaction stabilizes GRB2, thereby activating the Ras–mitogen-activated protein kinase (MAPK) signaling pathway. Consequently, escalated levels of GP73 intensify VEGF production in HCC cells and potentiate mitogenic signaling in vascular endothelial cells, fostering angiogenesis in the TME. Our findings propose that GP73 might serve as a novel target for anti-angiogenic therapy in HCC.